Development of comprehensive analytical methods for the assessment of toxic elements in selected Malaysian medicinal plants and their formulation - Khalid, Reem Saadi (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Analysis of arsenic (As), mercury (Hg), cadmium (Cd) and lead (Pb) in herbal medicinal products (HMP) encounter significant analytical challenges. This study aimed to develop, optimize and validate an analytical method for the determination of As, Hg, Cd and Pb in HMP using atomic absorption spectrometer (AAS). To overcome the limitations of hydride generation (HGAAS) and cold-vapor (CVAAS) techniques graphite furnace (GFAAS) was developed for the detection of As and Hg. The technique showed consistent levels of accuracy and precision in spiked HMP samples for As and Hg. The recoveries of arsenic measured by HGAAS – GFAAS were ranged between 81.3-91.5 % and 82.7-93% respectively. Mercury recoveries measured by CVAAS-GFAAS were ranged between 81.7-86.6 % and 80-86.7%. Sample preparation methods were developed by comparing three methods namely WD1, WD2 and WD3 which represented acid digestion with mixture of nitric-hydrochloric acids HNO3 – HCl in a ratio of 1:3 using conventional open vessel heating program, mixture of nitric acids - hydrochloric HNO3 – HCl in a ratio of 1:3 and a mixture of HNO3-H2O2 in a ratio of 4:1 using close vessel microwave digestion respectively. The comparison was conducted on HMP spiked with various concentrations of As, Hg, Cd and Pb standard solutions. Recoveries of As were 78.1-82.3 % , 90.5-92.8% , 91.4-93.3%; Hg 74.2-82.1, 87.1-91.9, 86.2-91.4; Cd 81-85,88.2-93.4,87.7-93.5 and Pb 78.1-82.2, 88.1-90.9, 88.7-92.6 for WD1,WD2 and WD3 respectively. The statistical analysis indicated good recoveries by microwave digestion methods WD2 and WD3 compared to method WD1 as they had given a significant high recoveries (p<0.05) compared to methodWD1. In further study to evaluated the effect of ammonium dihydrogen phosphate (NH4H2PO4) and palladium nitrate Pd (NO3)2 on the recovery values of As and Hg by comparing three digestion methods namely M1, M2 and M3 that represent microwave digestion without stabilizers addition, with addition of NH4H2PO4 and with addition Pd (NO3)2 respectively. Recoveries of As were ranged between 88.5-90.8%, 90-93.7%, 96.1-104% and Hg 88.3-91.8% ,87.4-93.5%, 95.5-100.1% for M1,M2 and M3 respectively. Statistical analysis showed significant high recoveries (p<0.05) for M3 compared to M1 for As and Hg analysis. Optimization of three digestion factors namely A, B and C time of digestion, reagent volume and temperature at high and low levels was performed by design of experiments (DOE) statistical approach. The optimum recoveries for As, Hg, Cd and Pb where found when factor A and C were at high level and factor B was low level. The developed method was validated by the analysis of As, Hg, Cd and Pb in apple leaves 1515 standard reference material (SRM) and applied for the analysis of some commercial HMP samples available in Malaysia. Excellent recoveries were obtained ranged between 98.2-102% for SRM. As was detected in 35%; Hg was found in 60%; Cd was found in 55% and Pb was found at 65% of the total number of the samples.